2011
DOI: 10.1038/hr.2011.111
|View full text |Cite|
|
Sign up to set email alerts
|

Prevention of gravidic endothelial hypertension by aspirin treatment administered from the 8th week of gestation

Abstract: The aim of this study was to evaluate whether low doses of aspirin (100 mg per day) administered to a homogeneous population of women early (8-10 weeks) during their first pregnancy improved the outcome of gestation hypertensive disorders. This study was performed at the Blida Hospital, where many early deliveries and pregnancy complications are observed. A total of 164 women were either treated (82) or used as controls (82). Treatment increased the gestation length by 12 days on average, thus triggering an ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 34 publications
2
38
0
1
Order By: Relevance
“…This finding is in agreement with a similar meta‐analysis published in 2010. Since then, four additional randomized trials that recruited high‐risk women prior to 16 weeks' gestation were published and their findings were consistent with our previous results. Moreover, the addition of two trials changed the conclusion regarding the effect of aspirin started after 16 weeks from insufficient evidence of effect to evidence of modest, but significant, reduction of the risk of pre‐eclampsia.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is in agreement with a similar meta‐analysis published in 2010. Since then, four additional randomized trials that recruited high‐risk women prior to 16 weeks' gestation were published and their findings were consistent with our previous results. Moreover, the addition of two trials changed the conclusion regarding the effect of aspirin started after 16 weeks from insufficient evidence of effect to evidence of modest, but significant, reduction of the risk of pre‐eclampsia.…”
Section: Discussionsupporting
confidence: 91%
“…Five studies reported PND as an outcome. The meta‐analysis demonstrated a significant reduction in the risk of PND (RR, 0.47; 95% CI, 0.25–0.88; P = 0.02; NNT, 92; 95% CI, 49–463) (Figure 2a).…”
Section: Resultsmentioning
confidence: 96%
“…Following review of the abstracts, 119 potentially suitable trials were selected for full review. Of these, 40 studies involving 34 807 participants, met the inclusion criteria and were included in the final analysis (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, only five studies on a combined total of 556 women were included in the final analysis because they fulfilled the three entry criteria: (1) treatment with aspirin or placebo initiated at or before 16 weeks of gestation, (2) information provided on preterm and term preeclampsia, and (3) judged for low-risk or unclear risk of bias. The control group received placebo in three of these studies and no treatment in two (table 1) [21,22,23,24,25]. …”
Section: Resultsmentioning
confidence: 99%